Problem-based Learning: Influence on Students' Learning in an Electrical Engineering Course - Yadav, Aman; Subedi, Dipendra; Lundeberg, Mary A.; Bunting, Charles F. (Journal of engineering education (Washington, D.C.), 2011)
Background Recently, there has been a shift from using lecture‐based teaching methods in undergraduate engineering courses to using more learner‐centered teaching approaches, such as problem‐based learning. However, research on the impact of these approaches has mainly involved student perceptions of the teaching method and anecdotal and opinion pieces by faculty on their use of the teaching method, rather than empirically collected data on students' learning outcomes. Purpose (Hypothesis) This paper describes an investigation of the impact of problem‐based learning (PBL) on undergraduate electrical engineering students' conceptual understanding and their perceptions of learning using PBL as compared to lecture. Design/Method Fifty‐five students enrolled in an electrical engineering course at a Midwestern university participated in this research. The study utilized a within‐subjects A‐B‐A‐B research design with traditional lecture as the baseline phase and problem‐based learning as the experimental phase of the study. Participants completed pre‐ and post‐tests surrounding the four topics covered in the study and also completed a Student Assessment of Learning Gains (SALG) survey. Result Results suggested participants' learning gains from PBL were twice their gains from traditional lecture. Even though students learned more from PBL, students thought they learned more from traditional lecture. We discuss these findings and offer implications for faculty interested in implementing PBL. Conclusion Given the limited research on the beneficial effects of PBL on student learning, this study provides empirical support for PBL. We discuss findings from this study and provide specific implications for faculty and researchers interested in problem‐based learning in engineering.